In Vitro Dissolution Kinetics of Bisoprolol Tablets Under Biowaiver Conditions - Logoyda, Liliya (Asian Journal of Pharmaceutics (AJP), 2019)
Introduction: Biowaiver procedure, nowadays, is a trend of Modern Biopharmaceuticals. The biowaiver approach based on Biopharmaceutical Classification System BCS is intended to replace bioequivalence in vivo studies. Bisoprolol is a medicine most commonly used for heart diseases, the beta blocker family of medications, and is of the Î²1-selective type. The Aim of the Study: The aim was to study the dissolution kinetics of bisoprolol tablets to assess their equivalence under conditions in vitro according to the biowaiver. Methods: The study of dissolution kinetics of drugs in the form of bisoprolol tablets has been carried out in accordance with the requirements of the â€œbiowaiverâ€ procedure, the recommendations of the SPhU, and the WHO requirements to assess the possibility of replacing the pharmacokinetic studies in vivo by tests in vitro. Results and Discussion: The possibility to use the recommendations of the â€œbiowaiverâ€ procedure for the registration of generics bisoprolol tablets has been found. The studies conducted have shown that bisoprolol can be referred to Class Ð† of the BCS, i.e., substances with a high biopharmaceutical solubility and a high penetration rate. It will allow conducting comparative studies in vitro to confirm the equivalence of drugs. Conclusions: The evaluated bisoprolol drugs fulfill biowaiver criteria for drugs containing BCS Class I active pharmaceutical ingredients. Both drugs are â€œrapidly dissolving,â€ both meet the criteria of dissolution profile similarity, f2 (i.e., the dissolution profile of the test product is similar to that of the reference product in pH 1.2, 4.5, and 6.8 buffers using the paddle method at 75 rpm), and both are considered to be in vitro equivalent without in vivo evaluation.